Peran Guru Pendidikan Pancasila dan Kewarganegaraan dalam Menanamkan Nilai Toleransi pada Sekolah Swasta Keagamaan - Laulita, Ulfa; Sanjaya, Dewa Bagus; Sustika , I Nengah (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to examine the role of Pancasila and Citizenship Education (PPKn) teachers in instilling tolerance values ??in students in private religious schools. Tolerance is a fundamental value in a pluralistic and diverse Indonesian society. This literature review analyzes the strategies and approaches used by PPKn teachers in developing attitudes of tolerance, the challenges faced in the context of private religious schools, and their impact on student character formation. The results of the study indicate that PPKn teachers have a strategic position as agents of transformation of tolerance values ??through contextual learning approaches, role models, and collaboration with various parties. The challenges faced include the potential for exclusivism of religious-based educational environments, intolerant external influences, and limited interaction with different communities. Research recommendations include strengthening the multicultural competence of PPKn teachers, developing more inclusive curricula and learning methods, and more intensive collaboration with families and communities.